The role of genes AMPD1, CNB and COL1A1 in the propensity to employment rowing. - Kozyrev A.V (Kharkov National Pedagogical University, 2011)
The question of the frequency distribution of polymorphic alleles of genes AMPD1, CNB and COL1A1. In the experiment, was attended by athletes, rowers qualifications at the age of 21 to 28 years, and people without experience of regular sport at the age of 20 to 22 years. Established that certain combinations of alleles can be recommended as a diagnostic complex genetic markers to assess the propensity to develop and display of strength, endurance and speed. It is shown that upon receipt of positive results may conduct a successful selection in rowing, the implementation of the individualization of the training process and improve its efficiency.